Ortodoks as slagspreuk en liberaal as etiket - Botha, Schalk Jacobus (Hervormde teologiese studies, 1994)
Orthodox as slogan and liberal as label Recently a debate on church and theology got underway in Die Hervomer, the official mouthpiece of the Nederduitsch Hervormde Kerk van Afrika. In this debate the words ‘orthodox’ and ‘liberal’ are frequently used. It is not the first time that these words are used within the historical context of the church in South Africa. This paper makes a short excursion into the history of the Nederduitsch Hervormde Kerk to establish how these words were used and what results their use brought for the Nederduitsch Hervormde Kerk.